Acupuncture with different acupoint combinations for chemotherapy-induced nausea and vomiting: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Gao, Lili; Chen, Bo; Zhang, Qiwen; Zhao, Tianyi; Li, Bo; Sha, Tao; Zou, Jinxin; Guo, Yongming; Pan, Xingfang; Guo, Yi
Abstract Background Acupuncture is beneficial for controlling chemotherapy-induced nausea and vomiting (CINV). However, the effect of different acupoint combinations on controlling CINV remains unknown. This study aims to compare the effects of distal-proximal point association and local distribution point association on controlling CINV. Methods/design The study is a single-center, randomized controlled trial. A total of 240 participants will be randomly divided into four groups. The control group will receive standard antiemetic only, whereas three acupuncture groups will receive four electro-acupuncture treatments once a day with the standard antiemetic. Acupuncture group I and II will receive distal-proximal point association ("Neiguan (PC6) and Zhongwan (CV12)", and "Zusanli (ST36) and CV12", respectively); Acupuncture group III will receive local distribution point association ("Shangwan (CV13) and CV12"). The primary outcome measures are the frequency and distress of nausea and vomiting. The secondary outcome measures are the grade of constipation and diarrhea, electrogastrogram, quality of life, etc. Assessment is scheduled from the day before chemotherapy to the fifth day of chemotherapy. Follow-ups are performed from the sixth day to the twenty-first day of chemotherapy. Discussion Results of this trial will help in evaluating the efficacy and safety of electro-acupuncture with different acupoint combinations in the management of CINV. Trial registration ClinicalTrials.gov identifier:NCT02478047 .